Increasing High School Students' Creativity in Local Wisdom-Based Environmental Studies Through the Project-Based Learning Model - Herni Arfida; Abdul Gani; Susilawati Susilawati; Ibnu Khaldun; Yusrizal Yusrizal (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Enhancing creativity through education enriched with local wisdom is essential, allowing students to delve into new ideas and information about chemical concepts through everyday phenomena. This research investigates the impact of a Project-Based Learning (PjBL) model infused with local wisdom on student creativity. A quasi-experimental design with pretest-posttest control groups was utilized. The participants were eleventh-grade students selected via purposive sampling. The study employed questionnaires and observation sheets as instruments. The procedure demonstrated that PjBL, enriched with local wisdom, significantly fosters student creativity by supporting authentic learning experiences and encouraging innovative ideas. In contrast, direct instruction predominantly centers on teacher-led activities, with minimal direct student engagement. The data analysis included average difference tests, N-gain, and percentage analysis. Results indicated a notable improvement in student creativity within the PjBL group compared to the control, with statistical significance at 0.000 < 0.05. N-gain scores were medium (0.44) for the experimental group and low (0.25) for the control. Creativity scores in the experimental group were high across all indicators—preparation, person, process, product, and press—ranging from 93.6 to 96.8. In contrast, the control group scored in the medium range from 66.7 to 72.6. This evidence suggests that the PjBL model effectively enhances student creativity by contextually integrating hydrocarbon chemical concepts with local wisdom. Therefore, this approach achieves curriculum goals and motivates educators and students to embrace and apply local wisdom creatively in their learning processes.